RADIOPROTECTIVE EFFECTS OF ALOE VERA ON HEPATOSOMATIC INDEX OF SWISS ALBINO MICE - DADUPANTHI, PRIYANKA (International Journal of Current Pharmaceutical Research, 2019)
Objective: In the living organisms, deleterious effects produced by ionizing radiations. Human exposure to ionizing radiations increased enormously because of rapid technological advancements. There is a need to protect humans against such effects of ionizing radiation. Protection against the deleterious effects of ionizing radiations by radioprotectors was studied, which may be of great help for human application. Present study was conducted to evaluate the modulating efficacy of prolonged administration of Aloe vera extract against gamma irradiation-induced toxicity in mice. Methods: Animals were given Aloe vera leaf extract orally 1000 mg/kg body weight/d for 15 consecutive days before radiation exposure (0.5, 3 and 5.5 Gy gamma radiation). Results: Mice were autopsied at day ¼, 1, 3, 5, 10 and 20 after irradiation to evaluate the radio modulator effect in terms of the hepatosomatic index. Conclusion: Aloe vera extract has a beneficial protective effect against radiation-induced oxidative stress.